2011
DOI: 10.1016/j.jtbi.2011.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Collective motion from local attraction

Abstract: Many animal groups, for example schools of fish or flocks of birds, exhibit complex dynamic patterns while moving cohesively in the same direction. These flocking patterns have been studied using self-propelled particle models, most of which assume that collective motion arises from individuals aligning with their neighbours. Here, we propose a self-propelled particle model in which the only social force between individuals is attraction. We show that this model generates three different phases: swarms, undire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
152
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(156 citation statements)
references
References 23 publications
3
152
1
Order By: Relevance
“…One explanation is that fish are attracted more strongly to neighbors in front of them than those behind, producing an asymmetry of leading and following that promotes group alignment (23). Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One explanation is that fish are attracted more strongly to neighbors in front of them than those behind, producing an asymmetry of leading and following that promotes group alignment (23). Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Instead, it appears that group alignment is achieved in some other way, possibly through attraction and repulsion rules and by fish following individuals in front of themselves. Models have already shown that such interactions can produce highly polarized groups (23,27). However, this is not to say that alignment rules are never adopted by this or other species.…”
Section: Discussionmentioning
confidence: 99%
“…Models with only attractive and repulsive interactions have long been studied in biology in the context of group formation and swarming [26 -28]. Still, only relatively few models have focused on the onset of collective motion without alignment based on purely repulsive and attractive interactions [29][30][31][32][33][34]. This is most probably because velocity alignment provides a simple and robust mechanism for the onset of polarized swarms, where individuals are able to agree on a common direction of motion.…”
Section: Introductionmentioning
confidence: 99%
“…The model described in this paper is one of a small set of swarm models that exhibit multiple group behaviors [9,29,27]. This research concentrates on the flock and torus behaviors; however, there are other types of swarm behavior seen in the literature.…”
Section: Related Workmentioning
confidence: 99%
“…Couzin's swarm behavior is analogous to a torus without orientation in our model, and the dynamic and highly parallel groups are simply two flavors of flocking. Strömbom [29] demonstrates that attractive forces between agents are sufficient to form swarms, flocks, and mills (torus-like formations where agents do not all rotate in the same direction). Strömbom also shows that adding a blind spot creates two additional group types: a torus and an interweaving chain-like structure.…”
Section: Related Workmentioning
confidence: 99%